Hybrid Learning in Mathematics Learning: Experimental Study in SMA Negeri 1 Pekanbaru - Zein, Mas`ud; M. Nuh, Zulkifli; Dardiri, Dardiri; Jasril, Jasril; Candra, Reski Mai; Hanafi, Imam; Thahir, Musa (Universitas Malikussaleh, Aceh Utara, Indonesia, 2019)
The Indonesian government is trying to implement a learning process based on information and communication technology. However, there are still weaknesses in the use of the internet in the learning process among students. Therefore, this article aims to describe the activities of students during the implementation of hybrid learning in mathematics learning and find out the results of student learning in mathematics through the application of Hybrid Learning. The research method used in this article is a true experimental design with a research sample of SMA Negeri 1 Pekanbaru students, whose schools have easy internet access. To obtain primary data from the field, tests are used to measure student mathematics learning outcomes. After each data is collected and tabulated, the data will be analyzed using statistical parametric analysis with the t test using the help of SPSS Version 18.00. The results showed that there were differences in student learning outcomes between those studying with the Hybrid Cooperative Learning method and students learning with conventional methods in SMA Negeri 1 Pekanbaru. The difference is confirmed again by the mean value of the experimental class 34.55 while the mean control class is 31.35. The results of this calculation indicate that the ability of the experimental class students is better than the control class students. This means that the value of the experimental class is better.